Two-Dimensional Nanomaterials for Biomedical Applications Emerging Trends and Future Prospects - Chimene, David (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.